2021
DOI: 10.1186/s12879-021-05906-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Pakistan: a systematic review of past decade

Abstract: Background During the last six decades, extensive use of antibiotics has selected resistant strains, increasing the rate of fatal infectious diseases, and exerting an economic burden on society. This situation is widely accepted as a global problem, yet its degree is not well elucidated in many regions of the world. Up till now, no systemic analysis of Antimicrobial resistance (AMR) in Pakistan has been published. The current study aims to describe the antibiotic-resistance scenario of Pakistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 81 publications
6
94
1
Order By: Relevance
“…Nonetheless, E. coli were sensitive to colistin 100%, imipenem 93.5% and meropenem 92%. Similarly, in 13 various studies of Pakistan demonstrate high resistance Klebsiella species against 2 and 3 generation antibiotics such as cefotaxime (82.%) and cefaclor (100%) (Bilal et al 2021). Whereas, Tauzina and coworkers found that E. coli strains were 43.7% resistant to amoxicillin and 3% to cephalosporin group isolated from meningitis affected children (Tauzin et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, E. coli were sensitive to colistin 100%, imipenem 93.5% and meropenem 92%. Similarly, in 13 various studies of Pakistan demonstrate high resistance Klebsiella species against 2 and 3 generation antibiotics such as cefotaxime (82.%) and cefaclor (100%) (Bilal et al 2021). Whereas, Tauzina and coworkers found that E. coli strains were 43.7% resistant to amoxicillin and 3% to cephalosporin group isolated from meningitis affected children (Tauzin et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…These resistant bacteria make even ordinary infections more difficult to treat and surgical procedure riskier to perform. Centuries of progress in improving health and economy is at stake due to antibiotic resistance [ 1 , 2 ]. If healthcare systems do not implement systematic interventions, by 2050, antibiotic resistance may inflict 10 million deaths per year around the globe and an economic loss of USD 100 trillion [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance is no longer only a problem of high-income countries, for instance, five Low- and Middle-Income Countries (LMICs) bear more than half (52%) of the burden of mortalities caused by neonatal sepsis associated with resistant strains of bacteria. In some cases, bacteria are resistant to up to 90% of antibiotics [ 1 , 2 ]. Over prescribing, limited surveillance or regulatory framework, and rampant poor practices of infection prevention and control incite a faster spread of resistant bacteria in LMIC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations